Pelestarian Lingkungan dan Peningkatan Nilai Ekonomi Limbah Melalui Sosialisasi dan Pelaksanaan Bank Sampah Banjar Umalas Kangin, Kuta Utara - Luh Gede Kusuma Dewi; Ni Komang Purwaningsih; Ni Luh Padmayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2022)
The socialization and implementation of this waste bank was carried out in Banjar Umalas Kangin, Kerobokan Klod Village, North Kuta District, Badung Regency. This service activity involves the participation of PKK administrators and members as well as a waste management company, namely BaliBagus Recycle. Banjar Umalas Kangin is a densely populated tourist area. This is one of the triggers for the increase in the volume of waste in this area. This garbage is usually thrown away by the community. However, with the waste bank program, it is hoped that it can contribute to increasing the economic value of the waste produced in this banjar area. This activity is also in line with the main PKK program.